Tourism industry methodology: potential for business development and regulation in countries of the world (Economics and region, 2024)
The article presents a substantiated methodology for the tourism industry, based on an analysis of the potential for business development and regulation in countries around the world. The functions of regulating the development potential of the tourism industry and the country's tourism business are presented in summary form. The regulatory aspects of the mechanism for stimulating entrepreneurial and investment activity are examined. The article presents models of regulation for business entities operating in the tourism industry. The "financing - regulation" matrix was constructed in the context of the interaction between the state and business entities in the tourism industry. A multifaceted methodology for the advancement of tourism enterprises on a global scale has been established. The paper proceeds to set out a series of strategic priorities for the development of the country's tourism business. Proposals regarding the potential for the development of the tourism business sector have been formulated.
Keywords: world experience; tourism business; development potential; digital transformation; methodology; regulatory measures; state; investments